The Digital Afterlife of a Melody: Exploring Discourse Patterns of Personal and Collective Grief via .Feast’s ‘O Tuan’ on TikTok - Anisa Julia Witana; Roziana Febrianita (International Journal of Social, Economic, and Business, 2026)
This study aims to examine and describe how the narrative of digital grief is constructed by TikTok users through content featuring the song “O, Tuan” by .Feast. Utilizing Rodney H. Jones’s digital discourse analysis approach, this research investigates the construction process through four main dimensions: text, context, action and interaction, as well as ideology and power relations. The results indicate that the construction of the grief narrative is achieved through the synchronization of the song’s audio-visual elements with slide texts and digital artifact visuals that function as a digital sympathy bridge, an emotional bridge that constructs private grief into a public narrative through collective netizen support. The findings also reveal that this narrative construction results in the practice of digital afterlife, where the song and TikTok features are used to maintain the existence of the deceased within the digital space. Ideologically, this construction reflects the formation of affective publics that position users as "Memory Guardians" to challenge the physical limitations of death. Audience interactions in the comment section demonstrate that the constructed grief narrative is not merely an expression of loss but an active communicative act that builds new norms of mourning in the digital era.